ANALISIS STRATEGI MARKETING MIX DALAM MENINGKATKAN OMZET PENJUALAN PADA PONDOK CIK ROZA KELURAHAN THE HOK - Anggraini, Mayang; Mubyarto, Novi; Anita, Efni; Munsarida, Munsarida (Program Studi Manajemen Keuangan Syariah, 2023)
This study aims to analyze the marketing mix strategy in increasing sales turnover at Pondok Cik Roza, Thehok Village. Source of data in this study are primary data through information froom the people studied, and secondary data through documentation, intervews and literature. This study used is a qualitative approach. The results show that the marketing mix strategy used at Pondok Cik Roza is 7p, namely marketing products that have characteristics at affordable prices, having quite strategic places, promoting through online or offline media. Having sufficient people, carrying out a good process and applying physical evidence that supports the Pondok Cik Roza business. The marketing mix strategy that does not work well is that the products offered often have vacancies, the promotions that are carried out are still not optimal and the physical evidence that has many shortcomings such as not having adequate parking space, the place is still narrow and others. This makes the sales turnover of Pondok Cik Roza not increase significantly. However, the owner of Pondok Cik Roza remains optimistic that his business will run smoothly by making improvements to the marketing mix strategy that has not been maximized.